Higher levels of circulating ANGPTL2 are associated with macular edema in patients with type 2 diabetes. Issue 6 (12th February 2021) - Yin, Ruili; Zhang, Ning; Zhang, Dawei; Zhao, Wenying; Ke, Jing; Zhao, Dong
Abstract : Abstract: Macular edema (ME) is an inflammatory disease characterized by increased microvascular permeability. Here, we proposed that plasma angiopoietin-like protein 2 (ANGPTL2) level may be related to the severity of ME patients with type 2 diabetes mellitus (T2DM). In this cross-sectional study, 172 T2DM patients were recruited and divided into clinically significant macular edema (CSME), non-CSME (nCSME), and control groups. Serum ANGPTL2 level was quantified by ELISA and best corrected vision acuity (BCVA) was detected. After adjust age, sex, body mass index (BMI), and duration of diabetes variables, ANGPTL2 performed statistics difference among CSME-, nCSME-groups, and control group (4.46 [3.97, 4.96, 95%CI] ng/mL in CSME group, 3.80 [3.42, 4.18, 95%CI] ng/mL in nCSME-group, 3.33 [3.03, 3.63, 95%CI] ng/mL in control, P  < .01). After adjustment of confounding factors, high levels of circulating ANGPTL2 were related with the diagnosis of ME, BCVA, and C reactive protein (CRP) through univariate regression analysis ( P  < .05). Meanwhile, in the multiple regression model, ANGPTL2 took the mainly effect proportion for the diagnosis of diabetic macular edema (DME), with a LogWorth value 3.559 ( P  < .001). Our study suggested that elevated circulating ANGPTL2 may be associated with the development of DME and the severity of visual impairment in patients with type 2 diabetes.